Plate convergence, crustal delamination, extrusion tectonics and minimization of shortening work as main controlling factors of the recent Mediterranean deformation pattern - D. Babbucci (Annals of Geophysics, 1997)
It is argued that the time-space distribution of major post middle Miocene deformation events in the Central-Eastern Mediterranean region, deduced from the relevant literature, can be coherently explained as a consequence of the convergence between the Africa/Arabia and Eurasia blocks. This plate convergence has mainly been accommodated by the consumption of the thinnest parts of the Northern African (Ionian and Levantine basins) and peri-Adriatic margins. During each evolutionary phase the space distribution of trench zones is controlled by the basic physical requirement of minimizing the work of horizontal forces, induced by plate convergence, against the resisting forces, i.e., the cohesion of the upper brittle crustal layer and the buoyancy forces at the consuming boundaries. The significant changes of tectonic styles which determined the transition from one phase to the next, like those which occurred around the Messinian and the late Pliocene-early Pleistocene, were determined by the suture of consuming boundaries. When such an event occurs, the system must activate alternative consuming processes to accommodate the convergence of the major confining blocks. The observed deformations in the study area suggest that this tectonic reorganization mostly developed by the lateral extrusion of crustal wedges away from the sutured borders. This mechanism allowed the translation of maximum horizontal stresses from the locked collisional fronts to the zones where consumable lithosphere was still present, in order to activate the next consuming processes. The extensional episodes which led to the formation of basins and troughs in the Tyrrhenian and Aegean zones are interpreted as secondary effects of the outward escape of crustal wedges, like those which occurred in response to longitudinal compressional regimes in the Apennines and Aegean regions.